Expression of human liver epoxide hydrolase in Saccharomyces pombe. - Jackson, M R (1988)
Human liver microsomal epoxide hydrolase cDNA was inserted into the yeast expression vector pEVP11. The resulting recombinant plasmid was introduced into Saccharomyces pombe. The epoxide hydrolase protein and enzymic activity was subsequently expressed and identified in the 105,000 g pellet after centrifugal fractionation of homogenized yeast cells. This method will provide a useful source of human liver epoxide hydrolase, avoiding the problems of obtaining human tissue.